A Remark on Weighted $(L^p ,L^r )$-Boundedness for Rough Multilinear Oscillatory Singular Integrals (Journal of Mathematical Study, 2023)
This paper studies the weighted $(L^p,L^r)$-boundedness for a class of multilinear oscillatory singular operators with real-valued polynomial phases and roughhomogeneous kernels belonging to $L{\rm log}^+L(S^{ n−1}),$ and establishes two criteria on thecorresponding weighted bounds for such operators.